2015
DOI: 10.1097/ico.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Keratoconus With New Dynamic Biomechanical In Vivo Scheimpflug Analyses

Abstract: In vivo biomechanical analyses (CST) at their current state only marginally improve KC screening protocols. Newly generated parameters such as the applanation length level and deflection length level might further improve early KC screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Although most of these parameters were significantly different in keratoconus and normal corneas, the overall AUC was less than 0.80 indicating insufficient predictive accuracy 23. Steinberg et al introduced ‘applanation length level’ and ‘deflection length level’ using Corvis, but they were also limited by a low discriminative power 27. In our study, we used a new Corvis software and identified novel parameters, namely DA ratio 2 (AUC 0.946), DA ratio 1 (AUC 0.937) and maximum inverse radius (AUC 0.954).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these parameters were significantly different in keratoconus and normal corneas, the overall AUC was less than 0.80 indicating insufficient predictive accuracy 23. Steinberg et al introduced ‘applanation length level’ and ‘deflection length level’ using Corvis, but they were also limited by a low discriminative power 27. In our study, we used a new Corvis software and identified novel parameters, namely DA ratio 2 (AUC 0.946), DA ratio 1 (AUC 0.937) and maximum inverse radius (AUC 0.954).…”
Section: Discussionmentioning
confidence: 99%
“…Most earlier studies produced an AUC lower than 0.900, [19][20][21] even though some of these studies refer to subclinical cases. 22 However, the dynamic Scheimpflug Corvis ST device is relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the analyzed CST parameters failed to detect abnormalities in the cases referred to as having subclinical disease. 1 However, we do have a few comments that should provide a positive insight into this important subject for our field.…”
Section: To the Editormentioning
confidence: 99%
“…Normal topography was defined as KISA less than 60%, I-S less than 1.4D, and Kmax less than 47D. 1 Even though this is relatively rare, it is possible that some of these cases have mild or susceptible forms of ectasia, because there are reported cases that, despite having normal topography and central corneal thickness, progressed to keratectasia after laser-assisted in situ keratomileusis (LASIK) 10,11 or photorefractive keratectomy. 12 Considering the preoperative state of stable LASIK cases with longterm follow-up would provide a more robust population for the normal control group.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation